THE INFLUENCE OF TRANSNATIONAL CORPORATIONS ON SOCIETY’S SAFETY BASED ON ACTIVITY OF AMAZON.COM IN POLAND AND GREAT BRITAIN - Siemiątkowski, Artur (Torun International Studies, 2017)
Social influence is not identical in each country or society, since activity of biggest corporations is so diverse. A lot of factors – both on the corporation side, as individual countries regulations – influence it, as well as societies and local communities specification. The aim of this article is to characterize the influence of transnational corporations on local communities safety on the example of Amazon.com corporation. Authors compared instances of two countries, in which this company runs le. Poland and Great Britain. Due to differences in conditions of functioning on these markets (e.g. on the level of economic growth or society), comparison of these two cases can give interesting results. An additional asset is the fact that author was an Amazon employee and he made many absorbing observations about the meaning of working in this corporation for members of local communities. The presence of transnational corporations in local area has a significant impact on local communities safety, because of influence on key needs of local societies members’ in terms of safety. The main thing is employment and salary. Very often huge logistics centres or manufacturing plants become the key employer in the region.